Multiple description encoding-decoding-based filtering for two-target tracking sensor networks under the FlexRay protocol - Zhang, Suqi; Kang, Yu; Fan, Sha; Zheng, Xiaoyuan (Nonlinear dynamics, 2025)
The distributed filtering problem based on multiple description encoding-decoding scheme under the FlexRay protocol is investigated for two-target sensor network. To effectively reduce the communication load and increase the network bandwidth utilization, the FlexRay protocol is used in this paper, leveraging the benefits of both Round Robin (RR) protocol and Try Once Discard (TOD) protocol. Additionally, the multiple description encoding-decoding scheme is utilized, where the transmission data are encoded into an index matrix. To improve the reliability of the transmission data, the number of row and column indices of the matrix are released to the sensor network through two independent channels. Under the FlexRay protocol and the multiple description encoding-decoding scheme, a distributed filtering method for two-target sensor networks is derived. The sufficient conditions to ensure the stability of the system are given. Finally, the effectiveness of the proposed protocol is verified by simulation examples.